2004
DOI: 10.1063/1.1697397
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a jet in cross flow at low velocity ratios

Abstract: This paper examines in detail the flow structure and associated wall pressure fluctuations caused by the injection of a round, turbulent jet into a turbulent boundary layer. The velocity ratio, r, ratio of mean jet velocity to the mean cross flow, varies from 0.5 to 2.5 and the Reynolds number based on the cross flow speed and jet diameter is 1.9ϫ10 4 . Particle image velocimetry is used to measure the flow and flush mounted pressure sensors installed at several locations used to determine the wall pressure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 15 publications
3
31
0
Order By: Relevance
“…Furthermore, detailed experimental studies of jets emitting from flat plates into ambient flows have shown that for low speed ratios the jet dominates the ambient flow. Hence the low pressure region is created solely by the induced separation of the ambient flow boundary layer [18,19]. That is, for low speed ratios the reduction in effective force is solely a function of the ambient flow speed and is independent of the jet exit speed.…”
Section: Performance On a Vehicle Undergoing Forward Motionmentioning
confidence: 99%
“…Furthermore, detailed experimental studies of jets emitting from flat plates into ambient flows have shown that for low speed ratios the jet dominates the ambient flow. Hence the low pressure region is created solely by the induced separation of the ambient flow boundary layer [18,19]. That is, for low speed ratios the reduction in effective force is solely a function of the ambient flow speed and is independent of the jet exit speed.…”
Section: Performance On a Vehicle Undergoing Forward Motionmentioning
confidence: 99%
“…Figure 1 shows data presented in terms of the speed ratio, however some authors have presented data to show that the decrease in effective force is solely a function of the ambient flow speed and therefore independent of the jet speed (and hence thrust) (Brix & Bussemaker, 1973;Karlikov & Sholomovich, 1998). In addition to this, detailed experimental studies of jets emitting from flat plates into ambient flows have shown that for small speed ratios the jet dominates the ambient flow and hence the low pressure region is created solely by the separation of the ambient flow boundary layer (Gopalan et al, 2004;Fric & Roshko, 1994). That is, for low speed ratios the reduction in effective force is solely a function of the ambient flow speed and is independent of the jet exit speed.…”
Section: Performance On a Vehicle Undergoing Forward Motionmentioning
confidence: 99%
“…Wake vortices are variously referred to in the literature as 'fire devils ' (McMahon et al 1971), 'spin-off vortices' (Wu et al 1988), 'fingers' (Lozano et al 1994), 'upright' (Kelso et al 1996), 'zipper' (Morton & Ibbetson, 1996), 'tornado-like' or Fric's vortices (Rivero et al 2001), and the 'wall-normal' vortices (Gopalan et al 2004). Although the wake vortices of the JICF have been investigated since the 1970s (e.g., McMahon et al, 1971), the question of their origin, statistics, and potential technological applications still persists.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern recognition analysis of the velocity field revealed strong fluctuations of CVP driven by these structures. Gopalan et al (2004) used particle image velocimetry (PIV), flow visualization, and wall pressure measurement to study the near-field of a water jet issuing from a fully developed turbulent pipe flow into a turbulent boundary layer, at velocity ratios 0.5 B VR B 2.5 and a Reynolds number of 19,000. For VR \ 2, a semicylindrical 'vortical shell' extending from the underside of the jet and connecting to the wall enclosed the reverse flow region.…”
Section: Introductionmentioning
confidence: 99%